Antimicrobial and Antioxidant Characteristics of Volatile Components and Ethanolic Fruit Extract of Prosopis farcta (Bank & Soland.) - Mohammad Ali Jahromi; Hamed Etemadfard; Zahra Zebarjad (Shiraz University of Medical Sciences, 2018)
The present investigation was conducted to study the volatile composition of essential oil, the radical scavenging and antimicrobial characteristics of the ethanolic fruit extract of Prosopis farcta (Bank & Soland.). The fruit essential oil was analyzed by means of gas chromatography/mass spectrometry (GC/Mass). Twenty seven compounds were identified which represents 97.3% of the total oil. Among the chemical components of the oil, the highest  percentage was recorded for 9,12-octadecadienoic acid ethyl ester (35.11%). Palmitic acid  (21.38%), cemberene A and nonanal (4.7%) and myristic acid (4.4%) were identified as the major constituents. P. farcta ethanolic fruit extract exhibited a high phenol content (61.55±0.07 mg gallic acid equivalent (GAE)/g of dry plant) while its total flavonoid content was found to be 17±0.08 mg quercetin equivalent (QE)/g of dry plant. Evaluation of antioxidant efficacy of ethanolic fruit extract was performed using DPPH (2,2-diphenyl-1-picrylhydrazyl), FRAP (Ferric Reducing Antioxidant Power) and ABTS+ (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) assays. In DPPH scavenging assay, IC50 value of the ethanolic fruit extract of P. farcta was found to be 62.45±00 µg/mL. The extract also exhibited a significant ABTS+ free radical inhibition (IC50, 53.24±0.03 µg/mL) while displayed a moderate reducing ability (IC50 =121.43±0.57 µg/ml) in FRAP assay. Results of antimicrobial screening revealed the higher inhibitory effect of ethanolic fruit extract against the growth of Staphylococcus aureus and Escherichia coli both with MIC values of 16 µg/ml when compared to other tested bacteria. A significant anti-candidial activity was detected for P. farcta ethanolic fruit extract (MIC50, 32 µg/mL) among the tested fungal species.